Simulation of Clinical Laboratory Process Improvement Based on ISO 15189 Standard - Bazan Rodriguez, Alexia Valery (2024)
The clinical analysis laboratory plays a crucial role in the diagnosis and prevention of diseases, consequently, the results of the examinations must be issued under optimal conditions of quality and precision that allow safe medical decisions to be supported. Accreditations such as ISO 15189 are instruments that allow laboratories to ensure, through their criteria and characteristics, results that meet quality standards, ensure traceability and have high reliability, furthermore, the analysis and application of this Standard contribute to the continuous improvement and optimization of resources in clinical laboratories, which generates greater productivity in the processes. In the present investigation, a simulation model of the laboratory service process in a medical center was designed to which proposed improvements were applied considering evaluated criteria of the ISO 15189 Standard. The simulation of the model was developed in the Arena software, executed the initial system model and the one proposed for comparison, where the optimization of process time was obtained, in particular the patient care capacity in the studied laboratory was increased by 33%, achieving an increase in 12 to 16 clinical analyzes performed per day. Likewise, the improvement in laboratory efficiency is directly related to the 32.3% increase in the medical center's monthly income from the tests performed in its laboratory. This demonstrates that the implementation of the ISO 15189 Standard can generate positive impacts that not only translate into the quality of the service but also the profitability of the laboratories.